<DATA REPORT>RIOMETER RECORDS OF 30 MHz COSMIC NOISE AT SYOWA STATION, ANTARCTICA IN 1979 - OSE, Masami; OJIMA, Seishin; KOMIYA, Noriaki (National Institute of Polar Research, 1980)
P(論文) departmental bulletin paper